Tanggung Jawab Pejabat Pembuat Akta Tanah (PPAT) dalam Membantu Pengurusan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) dan Pajak Penghasilan (PPh) untuk Proses Peralihan Hak atas Tanah dan Bangunan di Kabupaten Kampar - Teddy Aryanwara; Hasim Purba; Suprayitno (CV Rewang Rencang, 2025)
Pejabat Pembuat Akta Tanah plays a strategic role as a public official authorized to draw up authentic deeds as well as a party responsible for ensuring the fulfillment of tax obligations, particularly the Duty on the Acquisition of Land and Building Rights (BPHTB) and Income Tax (PPh), prior to the transfer of rights. However, in Kampar Regency, practices are still found involving manipulation of transaction values, discrepancies between the Tax Object Acquisition Value (NPOP) and market prices, as well as the involvement of PPAT in assisting the reduction of transaction values in order to minimize tax burdens. Such practices potentially lead to administrative violations and undermine the principle of legal certainty. This study employs a sociological legal research method with a descriptive-analytical nature. PPAT plays a juridical, administrative, and substantive role through the verification and validation of tax payment evidence to ensure legal certainty and prevent fiscal deviations. PPAT bears juridical, administrative, and moral responsibility to ensure the compliance of the parties and to maintain the professional integrity of the office. Therefore, PPAT is advised to enhance professionalism, while the local government together with the Regional Revenue Agency (Bapenda), the National Land Agency (BPN), and the Primary Tax Office (KPP Pratama) are expected to strengthen supervisory synergy both administratively and substantively. The public is also expected to increase legal awareness regarding BPHTB and PPh obligations with proper educational support from PPAT.